Determinants of factors affecting readiness of academic institutions to conduct knowledge translation in low- and middle-income countries - Kalbarczyk, Anna; Rao, Aditi; Alonge, Olakunle O. (Frontiers in Public Health, 2024)
Capacity building strategies have been used to improve uptake of knowledge translation (KT) activities among academic institutions, but little is known about their effectiveness, contextual responsiveness, and adaptability. Many of these strategies target individuals while few address institutional gaps. This research describes the determinants for conducting KT (or readiness to conduct such activities) at the institutional level across diverse LMIC contexts to inform the development of capacity building strategies.We conducted a survey to assess organizational readiness to conduct KT to public health researchers and practitioners from 6 academic institutions in Bangladesh, Ethiopia, DRC, India, Indonesia and Nigeria and members of a global knowledge-to-action working group. We assessed the frequency of barriers and facilitators to KT and their relationship to age, gender, country, and KT experience. We then performed logistic regression to identify determinants of five underlying factors demonstrated to influence KT readiness in LMICs (Institutional Climate, Organization Change Efficacy, Prioritization and Cosmopolitanism, Self-Efficacy and Financial Resource) along with their composite score, which represented an overall readiness score to conduct KT. 111 responses were included in the final analysis. Participants represented 10 LMICs; a majority were 30-49 years old (57%) and most were male (53%). Most participants had professional foci in research (84%), teaching (62%), and project coordination (36%) and 59% indicated they had experience with KT. Common facilitators included motivated faculty (57%) and dedicated personnel (40%). Funding (60%), training (37%), and time (37%) were the most frequently reported barriers. In the adjusted model, age, gender, country, and professional focus were significantly associated with at least one factor. Prior experience with KT was significantly and positively (OR=9.07; CI: 1.60-51.58; p<0.05) associated with the overall KT readiness to conduct KT.Different KT readiness factors are relevant for younger (institutional climate) vs. older (selfefficacy) academic professionals, suggesting value in cross-generational collaborations. Leadership and gender were both relevant for organizational change efficacy indicating a need to engage leaders and promote women to influence organizational change. Institutions in different countries may be at different stages of change; readiness assessments can be used to systematically identify needs and develop targeted strategies.